Amyloid pathology, small‐vessel disease, atrophy, and cognition in normal adults with type 2 diabetes. (December 2021) - Lesman‐Segev, Orit H.; Golan, Sapir; Ravona‐Springer, Ramit; Livny, Abigail; Lin, Hung‐Mo; Ouyang, Yuxia; Zadok, Maya; Hoffmann, Chen; Domachevsky, Liran; Beeri, Michal Schnaider
Abstract: Background: Various factors contribute to cognitive decline in older adults with type 2 diabetes (T2D). We assessed the association between imaging metrics of brain pathology (including global atrophy, small vessel disease, and amyloid deposition) with cognitive functioning in older adults with T2D. Method: Community‐dwelling, cognitively normal, older adults with T2D from the Israel Diabetes and Cognitive Decline Study with brain MRI and/or F18‐Flutemetamol amyloid‐PET were included. Gray matter (GM) and white matter hyperintensities (WMH) volume were extracted from high‐resolution T1‐weighted and fluid‐attenuated inversion recovery (FLAIR), respectively, using Statistical Parametric Mapping (SPM8). Amyloid PET was visually read and quantified using standardized uptake value ratio (SUVR) with the cerebellar gray and white matter as reference region. Global mean and lobar SUVR were extracted. Global cognitive functioning was assessed by neuropsychological testing and summarized into four domains including executive functions, attention, memory, and language, and an average of the four domains comprised global cognition. Linear regression models were used in a stepwise manner controlling for age, sex, education, HbA1c, and duration of T2D. MRI measures were also adjusted for intracranial volume. Result: 236 participants, 232 with MRI and 52 with amyloid‐PET were included, mean age 75 [66‐89], 39% females, 11 (21.1%) amyloid positive (Table 1). On average, participants had good glycemic control (mean HbA1C=6.7). An increase in global SUVR was associated with lower global cognition (Estimate=‐1.23, p=0.02). Additional adjustment for GM volume did not alter the results (Table 2). These results were driven by associations of SUVR with executive functioning (‐1.32, p=0.01), though a trend toward the same direction was also seen with attention (‐0.95, p=0.09), language (‐0.86, p=0.13), and memory (‐0.85, p=0.14) (Figure 1). Amyloid in all lobes contributed significantly to the associations (Table 2). No association was found between WMH volume and any of the cognitive outcomes (p‐values>0.21). Conclusion: In our cohort of normal cognitive older adults with well controlled T2D, amyloid load but not small vessel disease nor glycemic control was associated with cognitive functioning. This association was not mediated by GM volume suggesting other neurobiological substrates underlying the effect of amyloid on cognition in this population.